Implementation of Picture And Picture Method in Social Sciences Class IV at MIS Al-Istiqomah Atar Bawang Batu Ketulis Lampung Barat - Saputra, Rendy Rinaldy; Irawan, Asep; Yulia, Liyan Desi (Universitas Nusantara PGRI Kediri, 2019)
This research is motivated by the activities and learning outcomes of social studies at MIS Al-Istiqomah Atar Bawang which are lower than other subjects. The initial observation illustrates the possibility that causes this to occur, one of which is the motivation of students to take part in learning conducted using conventional methods is considered lacking. Based on the results obtained during observations, the authors are interested in introducing and practicing cooperative learning models that are assessed according to the criteria of elementary school students with the hope that there will be an increase in students' interest in attending lessons so that student achievement in social studies can increase. The study was conducted with a qualitative approach by observing and drawing conclusions based on observations made on students and teachers related to the learning methods applied. The collected data is then analyzed and concludes that the picture and picture learning model can increase students' interest and activity in teaching and learning activities. Based on the results of observations that have been made, it can be concluded that the picture and picture learning method is a learning model that is very appropriate to be applied to class IV students of MIS Al-Istiqomah. The application of the right learning model is expected to have a direct impact on increasing student achievement, especially on social studies subjects. Therefore, it is expected that teachers are able to understand and apply appropriate learning methods for students, and efforts are needed in facilitating the application of cooperative learning methods especially the method of picture and picture.